Loss of secondary-forest resilience by land-use intensification in the Amazon - Jakovac, Catarina C.; Peña-Claros, Marielos; Kuyper, Thomas W.; Bongers, Frans (The Journal of ecology, 2015)
1. Understanding how land-use intensification affects forest resilience is a key for elucidating the mechanisms underlying regeneration processes and for planning more sustainable land-use systems. Here, we evaluate how the intensification of a swidden cultivation system affects secondary-forest resilience in the Amazon. 2. Along a gradient of land-use intensity, we analysed the relative role of management intensity, soil properties and landscape configuration in determining the resilience of early secondary forests (SFs). We assessed resilience as the recovery level of forest structure and species diversity achieved by SFs 5 years after abandonment. We used as a reference the recovery level achieved by SFs subjected to the lowest intensity of use, given that these SFs are part of a dynamic system and may not develop to old-growth forests. Therefore, we interpreted a deviation from this reference level as a change in forest resilience. 3. The recovery of forest structure was determined by management intensity, while the recovery of species diversity was driven by landscape configuration. With increasing number of cycles and weeding frequency along with decreasing fallow period and patch area, SF basal area and canopy height decreased, regeneration shifted from a seed- to sprout-dependent strategy, and liana infestation on trees increased. With decreasing area covered by old-growth forest, species richness and Shannon diversity decreased. 4. Secondary-forest resilience decreased with land-use intensification, mainly mediated by the effect of management intensity upon regeneration strategies. Our findings demonstrate the – many times overlooked – importance of previous management intensity in determining the structure of SFs and highlight the importance of regeneration strategy for forest resilience. 5. Synthesis. Swidden cultivation supports people's livelihoods and transforms landscapes in the tropics. The sustainability of this system depends on ecosystem services provided by SFs that develop during the fallow period. Land-use intensification reduces the resilience of SFs and ultimately may drive the system towards an arrested succession state that holds a lower potential to deliver ecosystem services to the Amazonian people. Under an intensification scenario, the adaptation of management practices is needed to guarantee the resilience of swidden cultivation systems.